EFFECTIVENESS OF DIFFERENT DAMPING PAD GEOMETRIES IN REDUCING VIBRATION (Jurnal Teknologi (Sciences & Engineering), 2025)
This study aims to evaluate the effectiveness of different geometric shapes of damping pads in reducing vibrations, focusing on square, rectangular, triangular, and circular shapes. The pads were designed to have the same surface area, thickness, and materials to ensure a fair comparison. The main objective is to determine the most efficient shape for vibration reduction, especially in applications that require a quiet environment, such as vaporizer devices for asthma patients. Vibration velocity and displacement data were analyzed using MATLAB. The results showed that rectangular pads were the most effective, with a vibration velocity of 6.2 mm/s and a displacement of 0.0496 mm, achieving reduction percentages of 34.7% and 42.99%, respectively. The square shape demonstrated good stability with a vibration velocity of 7 mm/s and a displacement of 0.0565 mm, with reduction percentages of 26.3% and 35.2%. Triangular and circular pads were the least efficient in reducing vibrations. This study indicates that rectangular and square shapes are the most effective in reducing vibrations, making them suitable for applications that require a stable and quiet environment.